ANALYZE THE KNOWLEDGE INQUIRY SCIENCE PHYSICS TEACHER CANDIDATES WITH ESSENCE INQUIRY SCIENCE TEST INSTRUMENT OPTIKA GEOMETRY - Wawan Bunawan; Agus Setiawan (Jurnal Pendidikan Fisika, 2013)
The objective in this research to explore the relationship between ability of the knowledge essential features inquiry science and their reasons underlying sense of scientific inquiry for physics teacher candidates on content geometrical optics. The essential features of inquiry science are components that should arise during the learning process subject matter of geometrical optics reflectance of light on a flat mirror, the reflection of light on curved mirrors and refraction of light at the lens. Five of essential features inquiry science adopted from assessment system developed by the National Research Council. Content geometrical optics developed from an analysis of a college syllabus material. Based on the study of the essential features of inquiry and content develop the multiple choice diagnostic test three tier. Data were taken from the students who are taking courses in optics and wave from one the LPTK in North Sumatra totaled 38 students. Instruments showed Cronbach alpha reliability of 0.67 to test the essential features of inquiry science and 0.61 to there as on geometrical optics science inquiry.